2018
DOI: 10.1177/0954008318793181
|View full text |Cite
|
Sign up to set email alerts
|

High-performance polymer composites with enhanced mechanical and thermal properties from cyanate ester/benzoxazine resin and short Kevlar/glass hybrid fibers

Abstract: The investigation and design of new polymeric materials with an astonishing combination of properties are nowadays of great importance to facilitate the manufacturing process of high-quality products intended to be utilized in different applications and technical fields. For this intent, novel high-performance blend composites composed of the cyanate ester/benzoxazine resin blend reinforced by different proportions of silane-surface modified Kevlar and glass fibers were successfully fabricated by a compression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…It is in this context that the researcher groups have reported that the highest properties could be attained when the contents of the DCBA and BAa were, respectively, 90 wt% and 10 wt%, where the DCBA imparted its high thermal resistance, while the BA-a boosted the mechanical strength properties of the blend. [21][22][23] Consequently, appropriate amounts of the DCBA monomer (90 wt%) and the BA-a monomer (10 wt%) were carefully blended in a glass beaker and then melted in a vacuum oven at 120 C for 2 h. The obtained mixture was then well-mixed with the treated reinforcing materials at various weight amounts according to Table 1. After that, the uncured sandwiched composites were directly degassed under a vacuum oven at 140 C for 4 h to avoid the presence of what are called the voids and/or bubbles in the final cured samples that perhaps may have negative effects on the targeted physical and mechanical properties.…”
Section: Processing Of Polymer Blends and Their Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is in this context that the researcher groups have reported that the highest properties could be attained when the contents of the DCBA and BAa were, respectively, 90 wt% and 10 wt%, where the DCBA imparted its high thermal resistance, while the BA-a boosted the mechanical strength properties of the blend. [21][22][23] Consequently, appropriate amounts of the DCBA monomer (90 wt%) and the BA-a monomer (10 wt%) were carefully blended in a glass beaker and then melted in a vacuum oven at 120 C for 2 h. The obtained mixture was then well-mixed with the treated reinforcing materials at various weight amounts according to Table 1. After that, the uncured sandwiched composites were directly degassed under a vacuum oven at 140 C for 4 h to avoid the presence of what are called the voids and/or bubbles in the final cured samples that perhaps may have negative effects on the targeted physical and mechanical properties.…”
Section: Processing Of Polymer Blends and Their Compositesmentioning
confidence: 99%
“…20 Over the past few decades or even more, thermosetting resin blends composed of dicyanate ester of bisphenol-A (DCBA) and bisphenol-A based benzoxazine (BA-a) resins have captured an increasing interest in countless numbers of engineering applications, owing to their diversified properties, such as easy processability, near-zero shrinkage, low density, good corrosion resistance, high stiffness, high modulus and, most importantly, low cost. [21][22][23] In fact, it is broadly admitted that the polymer blending technique is by now deemed as an effective and economical pathway method to develop new materials, such that several investigations reported that the blending of DCBA with BA-a did result in new polymer materials possessing good properties as already cited above. [21][22][23] However, it needs to be said that the unmodified thermosetting resins or even their blends are featured by their high cross-linking density, which did mean that these materials might result in poor resistance to any applied mechanical loads, thus leading the researcher groups to find a reasonable solution in order to satisfactory fulfill the industrial demands for new eco-friendly materials that are nowadays much needed.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Currently, there is a paradigm shift in the lightweight structural application such as aerospace [1], automobile [2,3], maritime [4] and construction industries [5,6], where the use of traditional metallic structures are being substituted by advanced composites structures. The use of fiber-reinforced composites (FRC) is proliferating due to their preeminent specific mechanical properties [7][8][9][10], design flexibility [11], and fatigue life enhancement [12]. Additionally, the demand for FRC in these industries, especially aircraft and maritime, is growing expeditiously with anticipated demands to The bridging effect in complex shape structures, where laminates do not completely conform to the shape of the mold, is prevented by the use of an MSVB technique.…”
Section: Introductionmentioning
confidence: 99%
“…More and more researchers focused on the temperature effects of composites. 10,11 Cheng 12 analyzed the influence of temperatures on the bonding strength of carbon fiber/epoxy resin interface and obtained the interface strength with obvious temperature effect. At low temperatures, interface debonding was the main failure mode, and matrix failure was the main mode at high temperatures.…”
Section: Introductionmentioning
confidence: 99%